ҚАРАҚАЛПАҚСТАН ОЙКОНИМЛЕРИНИҢ ЖАСАЛЫЎЫ - Қурбанов, М.Д. (SCIENCE and SOCIETY, 2024)
The article analyzes general and various aspects of toponym formation and word formation. In toponymy, specific aspects of onomastic conversion, transonymization and composition are studied.
Keywords: onomastics; toponym; oikonym; word formation; toponym formation; oikonym formation; conversion; onomastic conversion; transonymization; composition